(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: The current study aimed to investigate the prophylactic potential of EBN compared to EDTA in mitigating Cd’s toxic effects on pregnancy rates and embryonic development in rats. Materials and Methods: Ninety-eight female rats (Sprague Dawley) were divided into donor and recipient groups, with donors further divided into seven subgroups, including negative control, Cd-exposed, EBN-treated, and EDTA-treated groups. Embryos from donors were transferred to recipient rats, with EBN and Cd administered for 4 weeks and EDTA given only in the last 5 days for the donor group. Results: Results showed significant differences in pregnancy rates and blastocyst quality. EBN at 120 mg/kg BW led to higher blastocyst production and better quality compared to Cd-exposed groups. The highest pregnancy rates in recipient groups correlated with the highest blastocyst scores from donors. Conclusion: EBN at 120 mg/kg demonstrated significant protection against Cd toxicity and its effect on pregnancy rates, embryo production, quality, and pre- and post-embryo transfer, surpassing the effects of both 90 mg/kg EBN and EDTA. This study provides empirical evidence in support of the conventional belief in the positive impact of EBN on female reproduction. J. Adv. Vet. Anim. Res., 11(4): 944–953, December 2024 http://doi.org/10.5455/javar.2024.k844